Nueva especie de Festuca L. sección Festuca (Poaceae) en la Península Ibérica, - Fuente García, Vicenta de la; Ortúñez Rubio, Emma (Lazaroa, 2000)
Fuente, V. de la & Ortúñez, E. New species of Festuca L. section Festuca (Poaceae) on the Iberian Peninsula. Lazaroa 21: 3-6 (2001). A new species of Festuca L., Festuca gredensis, is described from the Sierra de Gredos (Central Mountain System, Central Spain). Morphological, anatomical and chorological characters of the taxon are presented. estos caracteres en diversas poblaciones de los ma